The World Bank's Early Reflections On Development : A Development Institution Or A Bank? - Alacevich, Michele ca. 20. Jh (The World Bank, 2008)
Until the late 1960s, the World Bank presented itself as an institution devoted to making sound and directly productive project loans. Yet, during its very early years, some discussions developed inside the Bank regarding the possibility of issuing different types of loans, namely (i) loans aimed at tackling social issues ("social loans"), and (ii) loans aimed at providing foreign currency to address disequilibria in the balance of payments ("impact loans"). This paper brings together historical analysis and theories of organization development to study the housing issue as a case in point. The analysis reveals that the Bank was unwilling to lend for housing programs not because these were not sound - in fact, they were - but because they were geared toward achieving social welfare objectives and were not directly linked to productive investment projects, such as dams, power stations, and railroads. This early decision had a significant impact on the subsequent development of the Bank's view of policy-making: it locked the institution into a particular lending pattern, and deprived it of important intellectual resources. It was not until the late 1960s that the Bank began to take social issues into consideration, rather late compared with other multilateral institutions